Analysis of scrubber technology use to control SO2 emission in incinerators as a sustainable solution in plastic waste processing - Vivit Nur Indah Sari (Waste Handling and Environmental Monitoring, 2025)
Background: The use of wet scrubbers and dry scrubbers in incinerators using activated carbon and zeolite adsorbents is applied to control SO₂ emissions, serving as environmentally friendly waste processing tools. Methods: The principle of this test is that the exhaust gas from burning plastic waste with an incinerator is washed in a wet scrubber using water. Any remaining gas emissions are absorbed by zeolite and activated carbon through a dry scrubber. Testing of SO₂ exhaust gas emission concentrations is carried out on the incinerator, wet scrubber, and final chimney. Findings: The SO₂ exhaust gas concentration in incinerator combustion was 0.9685 mg/Nm³, the concentration after scrubbing using a wet scrubber was 0.1389 mg/Nm³, and the concentration after scrubbing using a wet scrubber and dry scrubber was 0 mg/Nm³. Conclusion: The use of a wet scrubber is effective in reducing SO₂ exhaust gas emission concentrations. The use of a dry scrubber is also effective in further reducing SO₂ exhaust gas emissions to zero. Novelty/Originality of this article: The novelty of this study lies in the combined application of wet and dry scrubbers with activated carbon and zeolite to achieve complete elimination of SO₂ emissions from plastic waste incineration, demonstrating a practical environmentally friendly approach.